Social Interactions Leading Role in Adopting the Fintech: A Case of Banking Sector - Riaz, Madiha; Mehmood, Abid; Shabbir, Uzair; Kazmi, Syed Mumtaz Ali (Pakistan Journal of Humanities and Social Sciences, 2023)
The objective of this study is to analyze the client behavior regarding the acceptance of FinTech services in the banking sector. The assumption is that social connections have a stronger impact on the acceptance of FinTech services and technology. To achieve this objective, several banks in Pakistan providing FinTech services were targeted, and a convenient sampling method was used to distribute questionnaires to bank users. After screening the questionnaires, a total of 377 responses were analyzed. Structural Equation Modeling was employed to analyze the data, and the results indicated that customers are more likely to adopt FinTech services if they trust the services, and this trust is developed through positive word-of-mouth from their social network. Additionally, the study found that customer education is a crucial moderator, as higher education levels lead to more informed responses. Educated customers showed a greater intention to adopt FinTech services, especially when they received positive feedback from friends and family. Based on these findings, it is recommended that service providers in lower-developing regions focus on building trust and utilizing social networks to promote the FinTech culture.